Teams Game Tournament (TGT) Model Influence on Students' Mathematics Ability Through Online Learning on Class VII Students of Hinai Junior High School - Zuhri Zuhri; Irwan Irwan; Arsip Perangin-Angin; Debby Fisela (Ridwan Institute, 2022)
The purpose of this study was to determine the effect of the Teams Game Tournament (TGT) cooperative learning model on students' mathematical abilities. This research was conducted at Public Junior High School 2 Hinai. The population in this study were all grade VII students of Public Junior High School 2 Hinai as many as 4 classes with a total population of 83 students. The sample in this study was class VII A which consisted of 20 people as the experimental class and class VII B amounted to 20 people as the control class. This type of research is quasi-experimental, the instrument used to collect data is a test containing 5 questions describing students' mathematical abilities. The data analysis technique used normality test, homogeneity, simple linear regression test, linearity, significance and hypothesis testing. Based on the hypothesis test, it is known that the r count value is 0.94 with r table 0.45, so r count > r table (0.94 > 0.45), which means that it accepts Ha, that is, there is an influence of the Teams Games Tournament (TGT) model on students' mathematical abilities in class VII Public Junior High School 2 Hinai.